Synthesis and Evaluation of 3-Halobenzo[b]thiophenes as Potential Antibacterial and Antifungal Agents - Prerna J. Masih; Tanay Kesharwani; Elivet Rodriguez; Mia A. Vertudez; Mina L. Motakhaveri; Terelan K. Le; Minh Kieu T. Tran; Matthew R. Cloyd; Cory T. Kornman; Aimee M. Phillips (MDPI AG, 2021)
The global health concern of antimicrobial resistance has harnessed research interest to find new classes of antibiotics to combat disease-causing pathogens. In our studies, 3-halobenzo[b]thiophene derivatives were synthesized and tested for their antimicrobial activities using the broth microdilution susceptibility method. The 3-halo substituted benzo[b]thiophenes were synthesized starting from 2-alkynyl thioanisoles using a convenient electrophilic cyclization methodology that utilizes sodium halides as the source of electrophilic halogens when reacted along with copper(II) sulfate. This environmentally benign methodology is facile, uses ethanol as the solvent, and results in 3-halo substituted benzo[b]thiophene structures in very high yields. The cyclohexanol-substituted 3-chloro and 3-bromobenzo[b]thiophenes resulted in a low MIC of 16 µg/mL against Gram-positive bacteria and yeast. Additionally, in silico absorption, distribution, metabolism, and excretion (ADME) properties of the compounds were determined. The compounds with the lowest MIC values showed excellent drug-like properties with no violations to Lipinski, Veber, and Muegge filters. The time-kill curve was obtained for cyclohexanol-substituted 3-chlorobenzo[b]thiophenes against Staphylococcus aureus, which showed fast bactericidal activity at MIC.